A clinical and statistical analysis of abscess in cellulitis. Issue 8 (22nd April 2021) - Okamoto, Osamu; Kai, Yoshitaka; Munemoto, Sekinori; Suzuki, Rui; Akishino, Kosuke; Hashimoto, Hiroyuki
Abstract: The features of abscess that forms in cellulitis patients were investigated. Among 449 cellulitis cases, about 15% developed abscess, and about 70% of teenaged patients were abscess cases. Furthermore, abscess in the younger age group occurred almost exclusively among male patients. The lesion was predominantly concentric at all ages in the abscess group and in teenagers in the non‐abscess group. In contrast, it was diffuse in patients ≥20 years old in the non‐abscess group. The clinical symptoms and laboratory values in the abscess group were generally more severe than those in the non‐abscess group, especially in the older age group. The abscess sizes increased with the initial area of the lesions. Most abscess cases received incision, and post‐incision ulcers were mostly conservatively treated. The duration required for treatment termination was >30 days longer in the abscess group than in the non‐abscess group. When post‐incision ulcers were conservatively treated, the duration until healing increased with abscess size. However, the durations did not significantly differ between the conservatively and surgically treated groups. When surgically treated, many ulcers healed within 19 days after operation and the outpatient follow‐up period tended to be relatively short. Most teenaged patients were student athletes, and thus needed an early return to competition. The main cause in these patients was bruising during sports, with rugby football the most common causative sport. Ulcer closure by operation was suggested to be preferable for shortening the outpatient follow‐up period, especially for student athlete patients.